Nucleation barriers for the cubic-to-tetragonal phase transformation in the absence of self-accommodation - Knüpfer, Hans; Otto, Felix (ZAMM, 2019)
The austenite-to-martensite phase transformation is characterized by the creation and growth of small nuclei of the new martensitic phase. Within a geometrically linear description and including an interfacial energy, we show that the minimal energy scales like in the volume V of the nucleus for when primarily only two martensite variants are present. This complements the findings in [Knüpfer, Kohn, Otto, CPAM 2012] where it has been shown that the minimal energy of the transient nuclei has the lower scaling if all three martensite variants are present. The higher scaling of the minimal energy is related to a failure of self-accommodation. The proof requires new analytical ideas and tools.